Point-of-Care Ultrasound as a Diagnostic Tool for Nutcracker Syndrome in Pediatric Emergency Department - Anıl Er; Burak Polat; Duygu Çiçek; Aykut Çağlar; Elif Gökbike Köseli; Tanju Çelik; İlker Günay; Hurşit Apa (Galenos Yayinevi, 2018)
Abdominal pain is one of the most common causes of admission to pediatric emergency department. Point-of care ultrasonography combined with appropriate history and physical examination provides rapid and accurate management of abdominal pain in emergency setting. Here, we report a 15-year-old girl with abdominal pain who was diagnosed with Nutcracker syndrome by the guidance of point-of-care ultrasound findings.